2002
DOI: 10.1029/2000ja003501
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of earthward flow bursts and plasmoid ejection during magnetospheric substorms

Abstract: [1] Examination of observations taken by radially aligned International Solar Terrestrial Physics spacecraft in the nightside magnetosphere on 9 July 1997 has revealed close temporal correlations between earthward flow bursts in the plasma sheet and the ejection of plasmoids. A onedimensional model of plasma sheet flow is applied to these observations to determine the time and location for the initiation of lobe flux tube reconnection. For the single clear flow burst-plasmoid pair observed during the first sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 80 publications
(160 reference statements)
4
62
0
Order By: Relevance
“…Auroral kilometric radiation (AKR) is widely accepted as one indicator of auroral activity and substorms (e.g. Slavin et al, 2002). We decided to examine AKR observations from the Wind WAVES instrument during the Wind dipolarization events, since this is the one substorm indicator that was guaranteed to be available during all of the dipolarization events.…”
Section: Substorm Onset Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auroral kilometric radiation (AKR) is widely accepted as one indicator of auroral activity and substorms (e.g. Slavin et al, 2002). We decided to examine AKR observations from the Wind WAVES instrument during the Wind dipolarization events, since this is the one substorm indicator that was guaranteed to be available during all of the dipolarization events.…”
Section: Substorm Onset Indicatorsmentioning
confidence: 99%
“…The signatures observed by satellites in various regions of the night-side magnetosphere during a typical substorm include bursts of high-speed earthward and tailward plasma flow, magnetic field dipolarizations, lowfrequency fluctuations of the electric and magnetic fields, the ejection of plasmoids, and energetic particle injections at geosynchronous orbit (e.g. Slavin et al, 2002;Nagai, 1982). Recent theories have suggested that the observations of dipolarizations and earthward flows in the magnetotail may be related to the formation of the substorm current wedge and the generation of the Pi2 pulsations observed by geosynchronous satellites and ground magnetometer stations (Shiokawa et al, 1998;Kivelson, 1999, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The reconnection process produces a magnetically confined structure (ie., looplike or helical magnetic topology) termed a "plasmoid" (Hones et al, 1984) that is ejected down the tail at high speed, as schematically depicted in Figure 7. As at the Earth, the observation of plasmoids in Mercury's magnetotail would provide direct information regarding the time of onset and intensity of magnetic reconnection (e.g., Baker et al, 1987;Slavin et al, 2002).…”
Section: Do Terrestrial-style Substorms Occur At Mercury?mentioning
confidence: 99%
“…This is a plasmoid, which is bounded by magnetic tension of the surrounding closed field lines connected at both ends to the Earth. Eventually, reconnection begins to process open field lines, at which point the plasmoid is released and can move downtail (Hones 1977;Baker et al 1996;Slavin et al 1999Slavin et al , 2002. In reality, if the reconnecting fields are not perfectly anti-parallel, then the plasmoid will in fact be a flux rope.…”
Section: Substormsmentioning
confidence: 99%